Financial Governance in Strengthening Post-Disaster Community Economic Resilience in Majene, Indonesia - Nur Khaerah; Shinta Alfiah Nur (Journal of Contemporary Governance and Public Policy, 2022)
The study of this article aimed to determine how the financial governance of the Asset and Regional Finance Agency in strengthening community resilience after natural and non-natural disasters in Majene Regency. This study used a qualitative method with a descriptive type of research through instrument data in the form of observation, documentation and interviews. The Regional Finance and Assets Agency in accordance with its main duties and functions carries out the mission, namely ‘Improving public services through good governance based on the rule of law’. The result showed that the Regional Finance and Assets Agency has the authority to manage regional finances that have been explicitly determined in the legislation has complied with the Regulation of the Minister of Home Affairs Number 113 of 2014 concerning Regional Financial Management which fulfills several important aspects, namely, planning, budgeting, administration, reporting and accountability. Based on the five stages, the Regional and Asset Finance Agency in Majene, Indonesia has complied with the five stages because it has gone through an integrated system.